2014
DOI: 10.1039/c3cp53649a
|View full text |Cite
|
Sign up to set email alerts
|

Marked enhancement in electron–hole separation achieved in the low bias region using electrochemically prepared Mo-doped BiVO4photoanodes

Abstract: Mo-doped BiVO4 electrodes were prepared by an electrochemical route for use as photoanodes in a photoelectrochemical cell. The purpose of Mo-doping was to improve the electron transport properties, which in turn can increase the electron-hole separation yield. The poor electron-hole separation yield was known to be one of the main limiting factors for BiVO4-based photoanodes. The electrochemical route provided an effective way of doping BiVO4, and the optimally doped sample, BiV(0.97)Mo(0.03)O4, increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
133
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 32 publications
14
133
1
Order By: Relevance
“…This suggests that the FeOOH layer induced the photostability of BiVO 4 /FeOOH. The use of FeOOH has been replicated in other studies for these reasons [29,42].…”
Section: Strategies Adopted To Enhance Reaction Kinetics In Solar Watsupporting
confidence: 50%
See 1 more Smart Citation
“…This suggests that the FeOOH layer induced the photostability of BiVO 4 /FeOOH. The use of FeOOH has been replicated in other studies for these reasons [29,42].…”
Section: Strategies Adopted To Enhance Reaction Kinetics In Solar Watsupporting
confidence: 50%
“…Park et al [42] reported that 3 at.% Mo doping on the V site almost doubled the absorbed photon-to-current efficiency (APCE), and also significantly enhanced the photocurrent density of bare BiVO 4 , from between 0.1 and 0.2 mA/cm 2 at 1.23 V vs. RHE, reaching a final photocurrent density of up to 1.0 mA/cm 2 at 1.23 V vs. RHE. After addition of an FeOOH OER co-catalyst, the photocurrent density increased even more to 3 mA/cm 2 at 1.23 V vs. RHE.…”
Section: Addition Of N-type Conductivity Dopantsmentioning
confidence: 99%
“…Such Mo-free, textured samples are designated ''noMo/T'' films. To assess the impact of incorporating molybdenum, an impurity known to improve the photocurrent of BiVO 4 electrodes, 18,21,26,30,31,33,34,37,40,42 we added Mo to untextured and textured BVO films (making ''Mo/U'' and ''Mo/T'' films, respectively) by spiking the spin coating solution with 2 at% MoO 2 (acac) 2 (see Experimental and Fig. 1c-e).…”
Section: Resultsmentioning
confidence: 99%
“…21,42 In this paper, we assume Z rxn,sulfite = 100% and negligible current doubling by sulfite. 59 Fig .…”
Section: àmentioning
confidence: 99%
“…8a). 60 Undoubtedly, the separation and transportation of the non-directional electrons are crucial factors for the further suppression on interfacial recombination. For this, given its high conductivity, rGO was introduced into FeOOH/P:BiVO 4 to transfer the electron to FTO (Fig.…”
Section: -50mentioning
confidence: 99%